Geografías afectivas Desplazamientos, prácticas espaciales y formas de estar juntos en el cine de Argentina, Chile y Brasil (2002-2017) - Depetris Chauvin, Irene (2019)
This book proposes traveling vicariously with documentary and fiction films directed by Mariano Llinás, Alicia Scherson, Karim Aïnouz, Marcelo Gomes, Cao Guimarães, José Luis Torres Leiva, Tiziana Panizza, Jonathan Perel, Gustavo Fontán, Ignacio Agüero, Raúl Ruiz, Patricio Guzmán and Enrique Ramírez. It attends to the very richness of cinema in its potential not to passively represent real physical spaces, but to reconfigure new ways of thinking and inhabiting open space geographies in the contemporary world from a perspective attentive to the dimension of affects. The landscapes, maps and itineraries configured by this set of films allow us to experience alternative notions of temporality and ways of connecting with others.